THE ASSOCIATIONS IN ESCHATOLOGICAL NARRATIVES INHABITING IN MARDIN AND ITS LANDSCAPE IN THE CONTEXT OF EXİSTENTIALISM - Şakire BALIKÇI (Fırat University, 2019)
The Associations in Eschatological Narratives Inhabiting in Mardin And Its Landscape in The Context of Existentialism With the studying of eschatology, the review texts including the narratives of apocalypse derived from Mardin and its landscape are primarily approached with existential philosophy, cultural identity and eschatology. In the entrance of study, the themes of existential philosophy and cultural identity are taken into the consideration. The eschatological narratives belonging to Mardin; the mutual significations witnessed in the societies possessing different cultural identities are evaluated in accordance with the wievs of personas from the communities of Muslim, Christian and Yazidi. The eschatological texts acquired from Mardin and its landscape are examined in two chapters. In the study, interpreting the texts as ‘the signs of apocalypse’ is highly probable as incidents which will show up on the edge of apocalypse or in the process of apocalypse…A number of statements, taking part in the texts including the theme of apocalypse derive its sources from holy scriptures. The other statements show up as mythical narrations pointing out that “Kızıltepe, a province of Mardin will turn into a hell with brutal numerous deahts”, “the mountain located in Mardin is named as ‘Massos’ will split in two than ‘Shahraman, the queen of Serpents and a sum of golden will come out of the mountain.”, “The mule will give a birth.” And “The rooster will lay eggs.” The texts giving a place to post-apocalypse are tackled in association with the belief in ‘Heaven and Hell’ and such texts are observed under the title of such particular themes above. In conclusion part, in mythical narrations, the phenomenon “death” as one of the essence of existential philosophy and ‘domestic and ethnic’ statements are must to be included within the narratives while interpreting the apocalypse, in other words, “the death of humanity and the earth.” are evaluated. In addition, “narative-mythic” narrations are deal within the context of cultural identity. In this chapter, with regard to the texts narrating the complete signs and the experiences of post-apocalypse and their transference to one culture to another, also the direction of cultural transference are tried to be found out.